Dietary Patterns Short Message Reminders’ Effect on Weight Gain in 1-3 Years Old Stunting Children - Samisatun Maulina, Siti; Setyoboedi, Bagus; Ningtyas, Woro Setia; Handayani, Samsriyaningsih (Universitas Islam Jember, 2023)
Stunting is a complex nutritional problem, in Indonesia is still quite high, in Lumajang district 2021 is 30.1%, this figure was still above the national average. Tempeh Community Health Center, as one of that handles stunting, in August 2022, there were 69 toddlers who experienced stunting. the main cause of stunting in Indonesia is chronic malnutrition which begins with inadequate weight gain which is influenced by diet. At the toddler age, dietarry patterns and habits begin to form, so they need to get used to regular and consistent dietarry patterns. This study aimed to analyze the effect of dietary pattern short message reminders on weight gain stunting children 1-3 years-old in the Tempeh Community Health Center. This study used an experimental design with a pre post control group design. Sampling used a consecutive sampling technique with randomization. The independent variable: dietary pattern short message reminders and dietary pattern, the dependent variable: weight gain. With SFFQ questionnaire research instruments, checklist sheets and digital weight scales. Data analysis with chi-square test. Chi square test revealed dietary pattern short message reminders affected weight gain, (X²=42.167, df=1, p=0.000, α=0.05). These data show that there was an influence of dietary pattern short messages reminders on weight gain in stunting children 1-3 years old.